2015
DOI: 10.1117/12.2189678
|View full text |Cite
|
Sign up to set email alerts
|

Limiting efficiencies of solar energy conversion and photo-detection via internal emission of hot electrons and hot holes in gold

Abstract: We evaluate the limiting efficiency of full and partial solar spectrum harvesting via the process of internal photoemission in Au-semiconductor Schottky junctions. Our results based on the ab initio calculations of the electron density of states (e-DOS) reveal that the limiting efficiency of the full-spectrum Au converter based on hot electron injection is below 4%. This value is even lower than previously established limit based on the parabolic approximation of the Au electron energy bands. However, we predi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Hot carriers are primarily generated with momentum parallel to the external field [31], which is generally parallel with the semiconductor interface in the case of an antenna, resulting in poor injection. Moreover, hot electron generation is also dependent on the plasmonic material employed [32,72,[76][77][78]. Several groups have explored the effects of the electronic structure of the metal on the generated carrier distributions [32,76] ( Figure 1F), and it has been shown that, in the interband transition regime, the electronic band structure of the metal plays an important role in determining both the energy and the momentum distribution of the generated hot carriers [32].…”
Section: Hot Carrier Generationmentioning
confidence: 99%
“…Hot carriers are primarily generated with momentum parallel to the external field [31], which is generally parallel with the semiconductor interface in the case of an antenna, resulting in poor injection. Moreover, hot electron generation is also dependent on the plasmonic material employed [32,72,[76][77][78]. Several groups have explored the effects of the electronic structure of the metal on the generated carrier distributions [32,76] ( Figure 1F), and it has been shown that, in the interband transition regime, the electronic band structure of the metal plays an important role in determining both the energy and the momentum distribution of the generated hot carriers [32].…”
Section: Hot Carrier Generationmentioning
confidence: 99%
“…To date, the series multijunction cell is the only proven solution to the spectral issue [see sections 11,13]. As also described elsewhere in this roadmap, there are several alternative concepts proposed to deal with the problem, from carrier multiplication to hot electron extraction [see sections 5,13] to parallel multijunction (as in a prism) [see sections 11,13] to thermal PV [see sections [15][16][17][18][19][20]. Likewise for the optical absorber thickness issue, various light-trapping innovations are being conceived and imple-mented to enable high absorption in ultrathin media.…”
Section: Plasmonics For Optical Energy Conversion -Michael J Naughtonmentioning
confidence: 99%
“…Proposals of photovoltaic up conversion and down conversion notwithstanding [see sections [13][14][15][16][17][18], current proposals are far below the required performance. Hence, in the foreseeable future, the focus will likely be on the types of nonimaging and aplanatic optics, gradient-index optics, and micromodularity (permitting optics precluded by common large-absorber collectors) that not only can raise solar conversion efficiency, but can render them more practical and amenable to large-volume production.…”
Section: Advances In Science and Technology To Meetmentioning
confidence: 99%
See 2 more Smart Citations